Mitochondria and oxidative stress in epilepsy: advances in antioxidant therapy - Ji, Delphine; Mylvaganam, Shanthini; Ravi Chander, Prathyusha; Tarnopolsky, Mark; Murphy, Keiran; Carlen, Peter (Frontiers in Pharmacology, 2025)
Epilepsy, affecting approximately 50 million individuals worldwide, is a neurological disorder characterized by recurrent seizures. Mitochondrial dysfunction and oxidative stress are critical factors in its pathophysiology, leading to neuronal hyperexcitability and cell death. Because of the multiple mitochondrial pathways that can be involved in epilepsy and mitochondrial dysfunction, it is optimal to treat epilepsy with multiple antioxidants in combination. Recent advancements highlight the potential of antioxidant therapy as a novel treatment strategy. This approach involves tailoring antioxidant interventions—such as melatonin, idebenone, and plant-derived compounds—based on individual mitochondrial health, including mitochondrial DNA mutations and haplogroups that influence oxidative stress susceptibility and treatment response. By combining antioxidants that target multiple pathways, reducing oxidative stress, modulating neurotransmitter systems, and attenuating neuroinflammation, synergistic effects can be achieved, enhancing therapeutic efficacy beyond that of a single antioxidant on its own. Future directions include conducting clinical trials to evaluate these combination therapies, and to translate preclinical successes into effective clinical interventions. Targeting oxidative stress and mitochondrial dysfunction through combination antioxidant therapy represents a promising adjunctive strategy to modify disease progression and improve outcomes for individuals living with epilepsy.